Tracheostomy in Tertiary Care Health Institution - Sigdel, B; Acharya, A; Ghimire, A (Journal of Nepal Health Research Council, 2014)
Background: Tracheostomy is the most obliging and one of the oldest operations in the history of surgery. It is channel between the trachea and skin in the midline in the neck. Most common indications are upper airway obstruction, mechanical respiratory insufficiency and pulmonary toileting etc.Methods: It is a retrospective study done in a teaching hospital in eastern Nepal from 2005-2008. Medical records of 175 tracheostomized patients were reviewed. Demographic variations, indications and outcome were recorded and analyzed.Results: Age ranged from 1 to 88 years. Most common age group was 21-30 years followed by 51-60 years. Common indications for tracheostomy were upper air way obstruction (34.3%), prolonged intubation (20%). Common diagnoses were tumor of larynx/hypopharynx (26.3%), infectious causes (20.6%) and cut throat (13.7%).Conclusions: Most common indication for tracheostomy in tertiary care health institution in Eastern Nepal was upper airway obstruction. Procedure is safe if done properly.Â Keywords: prolonged intubation; tracheostomy; upper air way obstruction.